The wedding witch ebook A novel. - Sterling, Erin (Graves Glen, 2024)
The New York Times bestselling author of The Ex Hex and The Kiss Curse brightens up the Winter Solstice with another delightfully spooky novel following Bowen Penhallow and the girl he feels strangely drawn to—especially when she becomes his only hope of salvation after a strong spell sends them to a Yuletide celebration... more than 50 years in the past. Bowen Penhallow has always been a loner, studying dark and ancient magic on a mountaintop in Wales. He prefers it that way. But when his friend Colin—who happens to be a ghost—asks him to attend a Yuletide wedding at a grand estate deep in the Welsh countryside, Bowen reluctantly agrees. Tamsyn Bligh is not a witch, but she makes her living off of them. As a procurer and seller of magical items, Tamsyn's business is not always above board, but she's been trying to fix that (mostly.) Bowen is an occasional customer—as well as the star of several of Tamsyn's dirtiest dreams—but she's been around enough witches to know that, as a human, getting involved with one is not the smartest idea. She's finagled an invite to the Witchy Wedding of the Century in the hopes of finally making a score big enough to retire. Just one priceless magical artifact from Tywyll House would set her up for life. But Tamsyn isn't the only one sneaking about in Tywyll House, and the mix of a very strong spell combined with a wedding mishap transports Bowen and Tamsyn into Tywyll House's past, to the Yuletide Celebration of 1958. As Bowen and Tamsyn work together to get back to the present, they must also face off with the origins of Tywyll House's haunting, the suspicions of their fellow witches...oh, and the fact that somewhere between the mistletoe and the bonfire, they might be falling in love.